Health system reforms in mature welfare states: tales from the north - Jean-Louis Denis; Susan Usher; Johanne Preval; Élizabeth Côté-Boileau (Universidade de Fortaleza, 2018)
Objective: This article has the objective show an essay on emerging themes in health system reforms, based on experience in Canada. Data synthesis: Reforms are the privileged mode of social change used by modern democratic societies. Persistent dysfunction and failure to adapt to emerging health needs and priorities within health systems in Canada provide a strong policy rationale to search for alternative strategies that might produce much-needed reforms. Three persistent challenges and opportunities for reform in Canadian health systems are discussed: the design of effective governance arrangements, the large-scale development and implementation of improvement and transformative capacities, and the leadership and engagement of the medical profession in working toward broad system goals. In exploring these challenges, we identify tensions that seem relevant to better understanding health system reform in mature welfare states. Conclusion: Addressing these tensions will require both a reinforcement of state and government capacities and stronger capacities at all levels of the health system to design and support change.